Alphabetical Effects on Political Careers. (December 2014) - Urbatsch, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Personal names have important consequences for many life outcomes, but their influence on political success is relatively unexplored. Yet widespread biases towards outcomes early in the alphabet and the propensity for some seniority lists (such as those in the United States House of Representatives) to privilege alphabetical position when politicians assume office simultaneously suggest that alphabetically early surnames may promote electoral success. Examining American governors and members of the federal Congress reveals that prominent elected politicians are, on average, earlier alphabetically than their average constituent. Furthermore, members of the House of Representatives are more likely to assume party leadership positions when they are earlier in alphabetical order, whereas members of the Senate (where alphabetical position plays no role in determining seniority) show no such relationship.